PENERAPAN PRINSIP PARTISIPASI DAN TRANSPARANSI DALAM PENATAAN DAN PENGELOLAAN PEDAGANG KAKI LIMA PASAR KLEWER SURAKARTA - Nurati, Dian Esti (Transformasi, 2018)
The latest condition of Street Seller arrangement in Surakarta City shows that it has not been arranged significantly. The data of Trading Service shows that out of 5,817 registered street sellers, some of them have not been arranged completely by Surakarta City government. Indeed, the arrangement cannot be done simultaneously, but it should be done gradually corresponding to the condition of budget existing in Surakarta City government. In addition, the arrangement should take the zone occupied by the Street Sellers into account. The ever growing number of Street Sellers will instead be a problem later, when it is not managed together. Surakarta City government has arranged street sellers seriously. In early 2017, Surakarta City government has completed the reconstruction of Klewer Market burnt in late 2014. Surakarta Trading Service arranges and manages street sellers in Klewer Market using participation and transparency principles. Participation principle, according to Verhagen (Mardikanto and Soebianto, 2015:81), is a special form of interaction and communication related to the sharing of authority, responsibility and benefit. Participation and transparency principles support the creation of Good Governance in which this concept application is often dependent on the organized cooperation between government and community such as Paguyuban (association) (Riswanda Imawan, 2002: 32). The growth of interaction and communication is reflected in the arrangement (organization) is adjusted with the condition of sellers before the fire. The process of validating data of Klewer Market sellers has been completed by City Government, indicating that there are 2,211 street sellers. The sellers to be arranged and to occupy the market starts to be registered, problem mapping is conducted, schedule is developed, requirements are communicated to all sellers, through both Paguyuban Pedagang Pelataran Pasar Klewer (P4K = Klewer Market Yard Seller Association), Himpunan Pedagang Pasar Klewer (HPPK = Klewer Market Seller Association), Komunitas Pedagang Pasar Klewer (KPPK = Klewer Market Seller Community), retailer, and street sellers around the market. The requirements specified to get kiosk in the permanent market are: showing Surat Hak Penempatan (SHP = Occupation Right Document), having Nomor Pokok Wajib Pajak (NPWP = Taxpayer Identity Number), and willing to pay retribution electronically (e-retribution). Surakarta City Government arranges sellers (traders) and Street Sellers in Klewer Market of Surakarta along with other stakeholders, corresponding to the objectives and programs as included into seller arrangement policy in Surakarta City. Referring to Participation and Transparency principle application, Good Governance is achieved in Surakarta City government, thereby expectedly can be more successful and professional in the next management.Keywords: Street Seller arrangement, Participation, Transparency, Good Governance